Estimation of malondialdehyde and catalase activity in pregnant women at IIMS&R Hospital, Lucknow, India - Niharika Singh; Saba Khan; Mohammad Mustufa Khan; Haseeb Ahsan; Roshan Alam (Acta Biochimica Indonesiana)
Background: During pregnancy, the physiological production of reactive oxygen species (ROS) is associated with a variety of maternal, placental, and fetal developmental functions. These functions are disrupted by excessive amounts of ROS, resulting to pregnancy complications. Different stages of pregnancy require a balance between oxidant and antioxidant production.